Untangling the knot: The information practices of enthusiast car restorers. (23rd July 2019) - Lloyd, Annemaree; Olsson, Michael
Abstract : A study of enthusiast car restorers is used to illustrate how an information practice approach can provide information science researchers with a richer, more nuanced understanding of the complex interrelationship between people, technology, and information. An ethnographic approach incorporating both semistructured interviews and in the garage ethnographic observation was employed. Analysis was undertaken using an inductive, thematic approach. The findings demonstrate that participants' information environments are rich and complex. Participants' accounts emphasized the corporeal and embodied nature of the restoration process, and this may account for why they privileged the social networks they had developed, often over many decades, over online resources and communities. The findings indicate that participants are engaged in much more than applied problem solving. What is also evident is that engagement in the social world of car restoration, and the networks of social knowledge sharing it affords, is significant for the emotional support it provides for older men who often lose these networks later in life. In a sense, the participants are not only rebuilding their cars but also their own sense of self.